A prospective study on the patient-specific factors affecting compliance in drug therapy of patients in Ward 11 for the period of January 15 to February 15, 2002 - Bermudez, Dan Millard B.; De Mata, Michelle P.; Eusebio, Lourdes I. (2002)
Noncompliance with drug treatment regimens is a major factor that affects the outcome of therapy. This study was designed to evaluate the extent of patient compliance and to identify the factors that contribute to noncompliance. All patients admitted and confined for a one-month period in Ward 11 are included in this prospective study. Demographics of the patient (age, gender, disease, days of confinement) as well as the number of medications, the regimen and the route of administration for each drugs were taken. The cost of each dose was also computed. Noting the number of dose taken compared to the number of dose prescribed allows assessment of compliance. SPSS version 10.05 statistical package was employed for all statistical calculations. The number of medications, days of confinement, regimen and cost of each dose significantly affects compliance (p<0.05). Strategies towards improving compliance both for the hospital and parents are discussed.
Thesis (B.S. Pharmacy)--University of the Philippines Manila, 2002
Keywords: Drug therapy; Patient compliance